PERENCANAAN PERKUATAN STRUKTUR GEDUNG KANTOR CAMAT PETANG AKIBAT PENAMBAHAN LANTAI DENGAN FRP (FIBER REINFORCED POLYMER) - I Putu Pandu Rusmana; I Gst. Nym. Putra Wijaya; I Made Ardantha (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
The existing building consisting of 3 floors if 3 floors is added will result in the existing structure not being able to withstand the workload due to the addition of the 3 floors so that the structure is needed. Structural reinforcement that is easily applied to reinforced concrete structures, one of which is FRP (fiber reinforcement polymer) which has a tensile strength of 7-10 higher than the tensile strength of reinforcing steel. In the office structure of the evening subdistrict after the addition of 3 floors there were several structural components that were not strong enough to withstand the added burden of B1 and B1A Beams on the pedestal which were 26 stems and 49 stems. The structure of the K1 column due to the addition of the floor also experiences an inadequacy in holding the load as much as 45 stems. Beams B1, B1A, and Column K1 performed structural reinforcement with FRP (fiber reinforcement polymer) with the following dimensions: Beams B1 and B1A reinforced with FRP tensile strength of 3400 MPa, FRP thickness of 1 mm, FRP width of 100 mm and FRP number the one used is 1 layer. The K1 column was strengthened with FRP tensile strength of 2100 MPa, FRP thickness of 0.5 mm, FRP width of 100 mm and the number of FRP used was 1 coil.